Miliary Tuberculosis as a Cause of Sudden Death in a Patient Misdiagnosed With Depression. Issue 5 (September 2016) - Haj Salem, Nidhal; Mesrati, Amine; Hadhri, Rim; Oualha, Dorra; Boughattas, Meriem; Aissaoui, Abir; Zakhama, Abdelfeteh; Chadly, Ali
Abstract : Introduction: Today, miliary spread remains one of the world's most lethal infectious diseases. Despite the availability of effective treatment for most cases, it is still a cause of death in our environment. Some cases of active tuberculosis (TB) are not identified until the patient is dead and an autopsy has been performed. We report an autopsy case of miliary TB and discuss the mechanism of death. Case Report: N.M. is a 24-year-old woman without any relevant personal medical or family history. She was admitted with fever of 40 days' duration. The fever was irregular, higher at nights, and associated with headache and anorexia. The patient did not give any history of coughing, hemoptysis, sore throat, joint pains, skin rash, abdominal pain, or rheumatic heart disease. The examination and the radiological investigations did not show any abnormalities. The patient was symptomatically medicated and allowed to return home. After 1 week, she was discovered dead in her bed. A forensic autopsy was requested. At necropsy, the lungs, liver, spleen, and kidneys were macroscopically palish, heterogeneous, and dotted with myriad of small seeds (1–2 mm). Mesentery was the seat of a large firm mass, adhering to the intestinal walls and the pancreas. The diagnosis of miliary TB was confirmed by histological examination. The toxicological screening was negative. Conclusions: Our case highlights a rare but important complication of TB, which is "TB-related sudden death." There is a need for more awareness of the disease, especially in the light of recent reports showing a growing incidence of extrapulmonary TB.